Community of Practice for Knowledge Sharing in Higher Education: Analysing Community of Practice Through the Lens of Activity Theory - Sie, Andi Bing; Aho, Anne Maria; Uden, Lorna (Springer International Pub., 2014)
Knowledge sharing is fundamental to learning among students. Learning and innovation occur when students are collaborating and able to share knowledge. Therefore students must be encouraged and be willing to share knowledge with one another. Although there are many benefits to knowledge sharing among students, in practice it is not easy to achieve. Communities of practice (COP) are an ideal platform for students to collaborate and share knowledge as they learn. However, creating and implementing an effective COP is not trivial. This paper describes our experience of using COP to promote knowledge sharing among undergraduate students working in a multicultural setting, analyses COP using activity theory, and outlines a design proposal for a COP using social objects.